2018
DOI: 10.1002/jobm.201800184
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel bacteriophage specific to Exiguobacterium indicum isolated from a plateau eutrophic lake

Abstract: Exiguobacterium is a versatile genus with potential in industry and agriculture. No bacteriophage that infects Exiguobacterium has been reported, despite its potential impacts on the utilization of Exiguobacterium. E. indicum EI9 was isolated from Dianchi Lake, a plateau eutrophic lake in China, which can significantly inhibit the growth of Microcystis aeruginosa. To isolate and characterize Exiguobacterium‐infecting bacteriophage, a virulent bacteriophage, DCEIV‐9 that specifically infects E. indicum EI9 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Another aquatic cellulolytic bacterium of the Phylum Firmicutes found in this study was Exiguobacterium indicum. Many previous reports showed that the E. indicum were isolated from various aquatic environments, such as melted water from glaciers in India [79], a hot spring in Vietnam [80], and a freshwater lake in China [81]. There were some strains of Exiguobacterium species that might produce cellulases [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Another aquatic cellulolytic bacterium of the Phylum Firmicutes found in this study was Exiguobacterium indicum. Many previous reports showed that the E. indicum were isolated from various aquatic environments, such as melted water from glaciers in India [79], a hot spring in Vietnam [80], and a freshwater lake in China [81]. There were some strains of Exiguobacterium species that might produce cellulases [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are still needed to understand the role of Clostridium sensu stricto in the karst reservoir. The OTUs 18 ( Bacillus ) and 24 ( Exiguobacterium ) affiliated with Firmicutes dominating the deep layer of DL Reservoir may be relating to their inhibiting effect on eukaryotic and other prokaryotic autotrophs, including Cyanobacteria 40 , 41 . The most abundant Verrucomicrobia-related OTU 23 ( Candidatus Methylacidiphilum) in DL Reservoir has been reported as a thermoacidophilic methanotroph in tropical and summer temperate lakes 32 , which was associated with autochthonous carbon production and able to conduct assimilatory nitrate reduction and reduce NO 2 − –N to N 2 O, suggesting their important role in carbon and nitrogen cycles 5 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It is shown in Table 1 that the largest number of anticyanobacterial Firmicutes are the Bacillus group, accounting for 77.3% of the total number of Firmicutes, while the remaining strains are from the genera Exiguobacterium [44,45] and Staphylococcus [35]. Li et al, (2015) revealed that Bacillus sp.…”
Section: Anticyanobacteriamentioning
confidence: 99%
“…The indirect attack mode has been observed in the numerous metabolites from most of the reported anticyanobacterial microorganisms, and the anticyanobacterial characteristics of these bacteria seem to be unique to M. aeruginosa. Up to now, the genus Acinetobacter [22,72,119] and Exiguobacterium [44,45,96], which firstly attach to M. aeruginosa and then cause serious damage to the cyanobacterial cell structure and morphology, are recognized as degrading M. aeruginosa by producing anticyanobacterial substances. Nevertheless, some anticyanobacteria can inhibit or kill green alga and cyanobacteria with an indirect attack simultaneously.…”
Section: Anticyanobacterial Modesmentioning
confidence: 99%